THE SOCIALIZATION OF ADOLESCENTS – AN INVESTMENT IN THE FUTURE ADEQUATE BEHAVIOR OF THE INDIVIDUAL - Daneva, Stanimira (E-Journal VFU, 2024)
Every human activity is realized in a social environment, which, in addition to providing conditions for the individual’s functioning, through the social situations that take place in it, also sets certain forms of behavior that are mandatory. As a result of their fulfillment or non-fulfilment, the individual is accepted or rejected by the environment. Therefore, effective functioning in any social environment requires optimal adaptation of the individual to it. Only this would allow him to fulfill his life goals and achieve high results. But this could happen if in early childhood the adolescent is optimally socialized in a suitable educational environment. The present article uses data from a scientific study of the adaptation of learners to three educational environments.